PELAPORAN KEUANGAN UMKM PSM DAN CABANG SESUAI DENGAN PSAK 65 - Putra, Yosep eka; W, Miftahusa’ada; Trinovila, Rahmi; Rahayu, Sri; Hidayat, Vegi Sabrina; Rahmi, Mega (PRISMAKOM, 2025)
This article discusses the financial recording and reporting practices of the Pekanbaru Shopping Mall (PSM) MSME and its branches, including Batusangkar, Bukit Gombak, and Cubadak. Based on observations and interviews, it was found that the recording system used is still very rudimentary and does not comply with PSAK 65 requirements for the preparation of consolidated financial statements. Transaction recording is limited to cash flow without account classification, without separation between head office and branches, and without the preparation of a structured income statement and balance sheet. Furthermore, internal transactions, such as shipments of goods from head office to branches, are not recorded in accounting, complicating the process of preparing consolidated reports and eliminating inter-unit transactions. These findings indicate the need for improvements to the accounting system at the PSM MSME to provide accurate, relevant, and standardized financial reports. By correctly implementing PSAK 65, the PSM MSME can improve the quality of financial information needed for decision-making and business control